Relationship of Training and Development, Political Interference, Technological Advancement and, Organizational Support: A Study of Punjab Police (Pakistan) (Journal of Governance and Development (JGD), 2023)
This study intended to examine the relationship of political interference,technological advancement and training and development with themoderating effect of organizational support on the performance of Punjabpolice Pakistan. Besides, this study used the quantitative research approachfor gathering of data. In the lieu of this, 159 survey questionnaires werecollected from SHOs (Station House Officers) of Punjab police (Pakistan).Moreover, PLS-SEM and SPSS techniques were applied to scrutinize thedata. The findings of the present study showed the significant positive effect oftechnological advancement and training & development on the performanceof Punjab police, meanwhile, on the other hand, the political interferencenegatively affecting the performance of Punjab police (Pakistan). Also,the findings of the study exhibited the significant moderating effect oforganizational support in the instance of technological advancement andtraining & development but in the case of political interference moderationdid not play any role.